Parasitemia and antibody response to benznidazole treatment in a cohort of patients with chronic Chagas disease - Moreira, Carlos Henrique Valente; Bierrenbach, Ana Luiza; Taconeli, Cesar Augusto; de Oliveira-da Silva, Léa Campos; Buss, Lewis F.; Keating, Sheila M.; Manuli, Erika Regina; Carvalho, Noemia Barbosa; Guastini, Cristina; Coco, Sonia Bakkour; Lindoso, José Ângelo Lauletta; Franco, Lucas Augusto Moyses; et al. (Frontiers in Parasitology, 2023)
Chagas disease, caused by Trypanosoma cruzi (T. cruzi), remains a significant public health concern in South and Central America. The primary treatment option, benznidazole (BNZ), presents challenges in assessing treatment success. To address this, we conducted a three-year observational study focusing on parasite clearance and antibody levels in patients with chronic Chagas disease undergoing BNZ treatment. While interpreting PCR results proved difficult due to fluctuating parasitemia levels, a notable finding emerged. We observed a consistent decrease in anti-T. cruzi antibody levels, particularly among patients classified as PCR-negative. This finding highlights the potential value of monitoring antibody decay as a proxy for understanding persistent parasite presence and ongoing antigenic stimuli. At the three-year follow-up, 90% of the patients tested negative, indicating successful suppression of parasites. However, the challenges in interpreting PCR results may be attributed to the assay's sensitivity and the age of the patient cohort. To optimize monitoring strategies and treatment outcomes for Chagas disease, further research is needed to explore the factors influencing these outcomes. This study underscores the need for surrogate markers of treatment success. It emphasizes the importance of monitoring antibody levels after treatment to gain insights into parasitological persistence and ongoing antigenic stimuli. By understanding the dynamics of antibody decay, we can better assess the effectiveness of treatment, explore new investigational compounds, and contribute to improved management of Chagas disease.